See how we roll : enduring exile between desert and urban Australia - Hinkson, Melinda (Global insecurities., 2021)
"Melinda Hinkson follows the experiences of Nungarrayi, a Warlpiri woman from the central Australian desert, as she struggles to establish a new life for herself in the city of Adelaide."--